Metabarcoding for bacterial diversity assessment: looking inside Didymosphenia geminata mats in Patagonian aquatic ecosystems - Suescun, Ana Victoria; Martinez-Cruz, Karla; Barret, Maialen; Cardenas, Leyla (My University, 2021)
The number of organisms that spread and invade new habitats has increased in recent decades as a result of drastic environmental changes such as climate change and anthropogenic activities. Microbial species invasions occur worldwide in terrestrial and aquatic systems and represent an emerging challenge to our understanding of the interplay between biodiversity and ecosystem functioning. Due to the difficulty of detecting and evaluating non-indigenous microorganisms, little is known about them and the processes that drive successful microbial invasions - especially when compared to macroinvasive species. Microalgae are one of the most abundant microorganisms in aquatic systems, and some are able to produce massive proliferations (mats) with significant impact on biodiversity and economic activities. Among microalgae invaders, Didymosphenia geminata is a benthic diatom that constitutes a major global threat for freshwater ecosystem conservation. Despite two decades of research, the cause of mat proliferations remains uncertain. It has been proposed that bacterial biofilm composition may contribute to successful attachment and consequently to proliferation. The aim of this work was to assess the bacterial diversity associated with the mat-forming diatom D. geminata in three aquatic ecosystems of the Chilean Patagonia by implementing genomic-based tools. Using a metabarcoding approach. we determined a core microbiota represented by 4 phyla, 16 families, and 20 genera. Proteobacteria (Alpha and Beta) and Bacteroidetes were the dominant phyla, followed by Cyanobacteria and Planctomycetes. At the lower taxonomic level, unidentified genera from the Comamonadacea family were the most abundant bacteria of the core microbiota. The bacterial composition we found was very similar, with some relative abundance changes, to that reported in a previous study of the bacterial diversity of biofilms from rivers contaminated with D. geminata in New Zealand. This geographical co-occurrence pattern between bacteria and D. geminata in different independent studies suggests that a specific microbiota may be associated with D. geminata distributions, establishment and proliferation. Our work serves as the starting point to design an experimental study that aims to determine whether these specific bacteria facilitate the establishment of the microalgae by creating favorable conditions or are the result of the diatom invasion.
Keywords: diatom; microalgae; microbiota; community assembly